PENYULUHAN PEMANFAATAN BUAH NAGA MERAH UNTUK PENDERITA DIABETES MELLITUS DI PUSKESMAS DELI TUA KABUPATEN DELI SERDANG - Rostiodertina Tina Girsang; Dewi Tiansa Barus (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
The prevalence of Diabetes Mellitus increases every year continuesly, data from the World Health Organization states that around 346 million people suffer from diabetes and Indonesia is ranked fourth in the number of DM sufferers in the world. Meanwhile, Indonesia is in the 7th rank of diabetes sufferers in the world. Dietary management of DM patients need to be modified, especially fiber and antioxidant intake. One of the fruits that can be used to improve diets for diabetes mellitus sufferers is dragon fruit which has the advantage of being rich in fiber and antioxidants and rich in vitamin C. Dragon fruit can control blood glucose levels so that it can prevent complications. The aim after counseling and demonstrations, it is hoped that fruit juice is made. Red Dragon can reduce glucose levels in diabetes mellitus clients and can be applied in the treatment of lowering blood glucose levels in diabetes mellitus sufferers. The activities carried out were in the form of counseling using leaflets and demonstrations on how to process and give red dragon fruit. There is a decrease in glucose levels in clients with diabetes mellitus after giving red dragon fruit for 14 days at the Delitua Health Center, Deli Serdang Regency. Thus, giving red dragon fruit for clients with diabetes mellitus is very effective in lowering glucose.